Background of the normative regulation on climate change in Peru - Franciskovic Ingunza, Millitza (2018)
This article develops the international normative background of one of the global and gravitational problems that has been affecting humanity as a whole without distinction of race, sex or socioeconomic strata, as is the climate change that generates besides environmental impacts, social impacts and We also take as a reference the scientific reports prepared by the Intergovernmental Panel on Climate Change (IPCC) for its acronym in English and conclude with a general analysis of the new Law on climate change. that our country has enacted in March of this year, becoming the first State that has enacted legislation on climate change.